Comparative evaluation of phasic and chemical antinociceptive action of a conventional and a novel anticonvulsants in experimental models of tail flick and formalin test - Kansal, Saurabh; Sirohi, Rohan; Agarwal, Ruchika (International Journal of Research in Medical Sciences, 2019)
Background: Some antiepileptic drugs have been shown to be clinically efficacious in treatment of neuropathic pain and are being used by clinician. Methods: This study determined the analgesic effect of gabapentin (a conventional anticonvulsant) and levitiracetam (a novel anticonvulsant) in rats in different types of acute and chronic nociceptive test like tail flick and formalin test and compared its potency with a conventional non opioid analgesic diclofenac. Results: Per oral administration of gabapentin produced no any marked effect on early phase response of formalin test but significantly suppressed the late phase response while levitiracetam produced no any type of significant effect in both phases. In tail flick test gabapentin as well as levitiracetam produced no any significant analgesic effect while diclofenac produced significant reduction of pain in tail flick test as well as in both phases of formalin test. Conclusions: Thus, we have observed that gabapentin produced antinociception in chronic pain as second phase of formalin test reflects chronic inflammatory pain while levitiracetam did not produce any type of antinociceptive effect as it could not suppress the pain significantly in both tail flick and formalin test.